Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade

Desafios para Moçambique - 2020 - Forquilha, Salvador (Instituto de Estudos Sociais e Económicos, 2020)
PARTE I – POLÍTICA Cabo Delgado e o risco sistêmico da Guerra em Moçambique / Severino Ngoenha, Giverage do Amaral e Alcido Nhumaio Face ao conflito no Norte, o que pode Moçambique aprender com a sua própria guerra civil (1976-1992)? Uma análise das dinâmicas da insurgência em Cabo Delgado / Salvador Forquilha e João Pereira Geografia eleitoral e insurgência em Cabo Delgado / Luís de Brito Paz e reconciliação em Moçambique: conjunturas críticas e dependência da trajectória / Bernhard Weimer e Natália Bueno Programas, sim, mas para fazer o quê? Uma análise dos manifestos eleitorais dos partidos políticos para as eleições moçambicanas de 15 de Outubro de 2019 / Michel Cahen A Governação Municipal em contextos de alternância política em Moçambique: Algumas notas a partir do município de Gurué (2014-2018) / Bernardino António PARTE II – ECONOMIA Finanças internacionais e formação do capitalismo nacional em Moçambique / Carlos Nuno Castel-Branco A economia de Moçambique e os conflitos e tensões à volta das condições de produção e reprodução agrícula / Carlos Muianga Tensões, conflitos e inconsistências nas relações entre a política fiscal e monetária em Moçambique / Yasfir Ibraimo Desafios e contradições para uma abordagem sobre trabalho e emprego em Moçambique / Rosimina Ali Investimento directo estrangeiro e o desenvolvimento socioeconómico em Moçambique: Dinâmicas, tensões e desafios / Michael Godet Sambo PARTE III – SOCIEDADE Protecção social e os principais obstáculos ao financiamento das empresas através da Bolsa de Valores de Moçambique / Moisés Siúta A segurança social em Moçambique: Conversa para boi dormir ou um instrumento de redistribuição viável? / Ruth Kélia Castel Branco Trabalho em função do género, trabalho migratório: Reformar os regimes do açúcar em Xinavane, Moçambique / Alicia Hayashi Lazzarini O trabalho doméstico em Moçambique: Uma década após a formalização / Ruth Kélia Castel Branco Pânico e medo: Desafio dos media moçambicanos na cobertura da COVID-19 / Celestino Joanguete PARTE IV – MOÇAMBIQUE NO MUNDO Ugandeses e Tanzanianos do Al-Shabaab: Um olhar à dimensão internacional do conflito em Cabo Delgado / Sérgio Chichava Ligações ecnómicas entre a África do Sul e Moçambique: Dionâmicas pós-coloniais e pós-Apartheid entre 1990-2002 / Carlos Nuno Castel-Branco
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade